Pengaruh Aplikasi Marbel Huruf Terhadap Motivasi Belajar Dan Kemampuan Mengenal Huruf Di RA Nurul Huda Bayongbong Garut - Resiana, Rani Surya; Asvia, Silma (LP2M STAI Al-Musaddadiyah Garut, 2024)
In general, it is known that activities at RA Nurul Huda have placed more emphasis on technical reading and writing skills. This research aims to determine the effect of the Marbel Letter Application on learning motivation and the ability to recognize letters in early childhood. The research used is quantitative research, where quantitative research is more concerned with depth of data and can record as much data as possible. The results of the research that has been carried out have obtained significant values, where the post-test coefficient of determination (R2) test value is 69.2% higher than the pre-test value of 40.8%. This shows the influence of the Marbel Letter Application (X) on learning motivation (Y1) and the ability to recognize letters (Y2) in early childhood. Keywords: Marbel Letter Application, Learning Motivation, Ability Recognizing Letters, Early Childhood